Tourist experience in Halal tourism: what leads to loyalty?. Issue 14 (18th July 2021) - Suhartanto, Dwi; Dean, David; Wibisono, Nono; Astor, Yackob; Muflih, Muhammad; Kartikasari, Ani; Sutrisno, Rivan; Hardiyanto, Nugroho
ABSTRACT: Although tourist loyalty has been reported to be crucial in Halal tourism, there are few studies examining Halal tourist loyalty. This study assesses how tourist loyalty is determined by Halal experience, experience quality, perceived value, and satisfaction. For this purpose, a survey was drawn from literature, designed to examine the hypotheses proposed, and conducted in Bandung, Indonesia where a total of 522 responses were gathered from Muslim tourists. Through an exploratory factor analysis, this research reveals that tourist Halal experience dimensions consist of Halal accommodation, Halal facilities and service, and people in the destination. The partial least squares modelling reveals that Halal experience, perceived experience quality, perceived value, and satisfaction are important drivers of Halal tourist loyalty. Further, the results of this research disclose that amongst the dimensions of Halal experience, the people in the destination dimension has the biggest impact on tourist experience with the visit, perceived value, satisfaction, and loyalty. These findings offer unique insights both for theoretical development as well as for tourist operators, especially those involved with Halal tourism.